Taxonomía de algunos microtéidos de Venezuela (Squamata), II: Situación nomenclatural de Prionodactylus ampuedai y Prionodactylus phelpsorum - Abraham Mijares-Urrutia (Revista de Biología Tropical, 2000)
New records of the poorly known microteiid lizard Prionodactylus ampuedai, morphological variation, and new data on natural history are reported. We report the loss of the holotypes of P. ampuedai and P. phelpsorum, and designate a neotype for the former. Euspondylus goeleti is resurrected from the synonymy with E. phelpsorum and this latter is transferred to the genus Prionodactylus.